Influence of laser energy density on geometrical forms produced by laser metal deposition of PH 13-8 Mo stainless steel (Journal of Additive Manufacturing Technologies, 2021)
Additive manufacturing (AM) is getting more popular in many industries due to direct manufacturing facilities, design flexibility and effective lead time. Directed energy deposition (DED) is a variation of AM and laser metal deposition (LMD) is regarded as a DED process and it uses laser as a heat source to melt and deposit the raw material fed through a nozzle in the powder form.  This paper presents a research work that investigates the forms of laser metal deposited parts in S-shaped using PH 13-8 Mo stainless steel powders. Experimental work was conducted to produce S-shaped single bead walls with main process parameters affecting the energy density. The results have been discussed by considering the energy density levels as low, medium and high. It is clear to observe that the low energy density level parameters produce no or improper S-shaped walls. However, high energy density level parameters produce relatively well deposited walls but the geometrical forms of the walls are not steady due to heat accumulation during the deposition. Balling on the deposited walls can be seen in each energy density level. This defect occurs when there is insufficient heat energy to melt and deposit the powder from the moving nozzle.
Keywords: Additive manufacturing; Laser metal deposition; PH 13-8 Mo stainless steel